The crystal structure of Histidinium hydrogensquarate, C10H11N3O6 - Kolev Tsonko; Peeva Martina I.; Bogdanov Ivan P.; Ognyanov Iliyan V.; Atanasov Atanas G.; Tzvetkov Nikolay T. (Zeitschrift für Kristallographie - New Crystal Structures)
C10H11N3O6, monoclinic, P21/c (no. 14), a = 7.4928(12) Å, b = 14.860(3) Å, c = 11.0593(18) Å, β = 109.465(5)°, V = 1161.0(4) Å3, Z = 4, Rgt(F) = 0.0439, wRref(F2) = 0.1060, T = 300.0(2) K.